Diode Laser Ear Piercing: A Novel Technique - Suseela, Bibilash Babu (J Cutan Aesthet Surg, 2016)
Earlobe piercing is a common office room procedure done by a plastic surgeon. Various methods of ear piercing have been described. In this article, we describe a novel method of laser ear piercing using the diode laser. An 18-year-old female patient underwent an ear piercing using a diode laser with a power of 2.0 W in continuous mode after topical local anaesthetic and pre-cooling. The diode laser was fast, safe, easy to use and highly effective way of ear piercing. The advantages we noticed while using the diode laser over conventional methods were more precision, minimal trauma with less chances of hypertrophy and keloids, no bleeding with coagulation effect of laser, less time taken compared to conventional method and less chance of infection due to thermal heat effect of laser.